Stability inside hen eggs of a Salmonella enterica serovar Enteritidis bacteriophage - Robeson, James; Valencia, Martina; Retamales, Julio; Borie, Consuelo (Electronic Journal of Biotechnology, 2011)
Background: Bacteriophages are viruses that infect bacteria and therefore are widespread in nature. Those that lyse the pathogen Salmonella enterica serovar Enteritidis (SE) should be expected in niches in which this bacterium thrives, among others the avian egg. Furthermore, bacteriophages could remain viable in this milieu. Results: Upon artificially infecting hen eggs with the SE bacteriophage f18 we found that the bacteriophage titer remains stable at least for up to 144 hrs post-infection , both in yolk and albumen at 25ºC. Conclusion: Bacteriophage f18 withstands the physico-chemical conditions of the egg inner milieu and could be considered for SE-controlling measures in the poultry industry.